Investigation of flow around bluff body using lattice Boltzmann method - Shaifulnizam, Sharif (2009)
Flow around a bluff body, a square cylinder, has extensive significance in engineering. The main objective in this thesis was to investigate a flow around bluff body using a Lattice Boltzmann Method. To achieve this objective, various values of Reynolds numbers have been a parameter to see the flow characteristic around bluff body in the channel with geometry mesh. There are two types of square cylinder condition for this case study which is single square cylinder and double square cylinder side by side. For both condition, square cylinder have been place in channel. The simulation for both cases was studied under isothermal lattice Boltzmann method condition in which we investigated computationally in a two-dimensional configuration using a fluid dynamics program. The different Reynolds numbers has given the different flow characteristic around the square cylinder. From the simulation, discussions have been made, and conclusion for this thesishas been obtained. Finally, for future investigation, the correlations obtained from this numerical result could be used to investigate the flow around bluff body.